Typical risk pattern for anterior cruciate ligament injury is largely present in competitive athletes: biomechanical screening through wearable sensors - Di Paolo, S.; Bragonzoni, L.; Della Villa, F.; Grassi, A.; Zaffagnini, S. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to investigate the presence of biomechanical risk patterns for Anterior Cruciate Ligament (ACL) injury in a healthy population during the execution of high-dynamics movements. Competitive athletes (n=34) performed a test battery, including single-leg landings, sprints, and cuts. Kinematics was assessed through wearable sensors, and movements exhibiting risk patterns were searched through multiple joint thresholds based on the current literature on ACL injury mechanism. A large portion of the athletes exhibited dangerous patterns in one (94%) or more movements (up to 11). The incidence was higher at initial foot contact and for the movement performed with the non-dominant limb. The early identification of at-risk athletes might support ACL professionals and promote preventative training strategies focused on the increase of movement quality.